+0  
 
0
217
1
avatar

what is -sqrt 48 + sqrt 108

Guest Oct 6, 2017
 #1
avatar
+1

Simplify the following:
sqrt(108) - sqrt(48)

sqrt(48) = sqrt(2^4×3) = 2^2 sqrt(3):
sqrt(108) - 2^2 sqrt(3)

2^2 = 4:
sqrt(108) - 4 sqrt(3)

sqrt(108) = sqrt(2^2×3^3) = 2×3 sqrt(3):
2×3 sqrt(3) - 4 sqrt(3)

2×3 = 6:
6 sqrt(3) - 4 sqrt(3)

6 sqrt(3) - 4 sqrt(3) = 2 sqrt(3):
2 sqrt(3)

Guest Oct 6, 2017

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.